2016
DOI: 10.1055/s-0042-102457
|View full text |Cite
|
Sign up to set email alerts
|

Azapirones for Attention Deficit Hyperactivity Disorder: A Systematic Review

Abstract: It remains unclear whether buspirone use has benefit for ADHD patients and therefore further evidence is needed for better clinical use of buspirone in patients with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Available systematic reviews found only preliminary evidence (few studies with a low sample size and methodological issues) to support the efficacy of bupoprion,25 buspirone,26 aripiprazole,27 magnesium28 and reboxetine29 in adults with ADHD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Available systematic reviews found only preliminary evidence (few studies with a low sample size and methodological issues) to support the efficacy of bupoprion,25 buspirone,26 aripiprazole,27 magnesium28 and reboxetine29 in adults with ADHD.…”
Section: Resultsmentioning
confidence: 99%
“…Only preliminary results on efficacy are available for bupropion,25 buspirone,26 aripiprazole,27 magnesium,28 and reboxetine29…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis from 1999 also suggested similar findings for clonidine [127]. However, as for stimulants, meta-analyses and Cochrane review stated that the efficacy of some of the nonstimulants cannot be established due to short follow-up time, low quality, limited number of studies, sample sizes, and heterogeneity [128130]. There is thus disagreement on how to interpret the literature also for nonstimulants.…”
Section: Resultsmentioning
confidence: 99%
“…There is, however, an interesting controversy on how solid the trial evidence on ADHD medication efficacy is. Several reviews on both children and adults, and for both stimulant and nonstimulant pharmacotherapy, conclude with caution as to conclusions on efficacy [123, 124, 128, 130, 135, 139, 157, 158].…”
Section: Discussionmentioning
confidence: 99%